Meningkatkan Aktivitas Belajar Peserta Didik Menggunakan Model Pembelajaran Inkuiri Terbimbing di SMP Negeri 8 Pontianak - Wahyuni, Eko Sri; Titin, Titin; Nadia, Fitria Salwa (Jurnal Ilmiah Edukatif, 2025)
This study was motivated by the learning activities of students which were classified as very poor because the learning process that took place did not make students the subject of learning but was still centered on the teacher and the learning methods used were still lectures. The purpose of this study was to increase students' learning activities using the guided inquiry learning model in class VII D SMP Negeri 8 Pontianak. This type of research is Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of planning, action, observation and reflection stages. The research subjects were 35 students of class VII D SMP Negeri 8 Pontianak. The instruments used in this study were observation sheets of students' learning activities. Data analysis was done by descriptive analysis. The results showed that the percentage of students' learning activities was 74.29% (good category) in cycle I and 85.71% (very good category) in cycle II. Based on these results, it can be concluded that the learning activities of students in class VII D can increase through the application of guided inquiry learning model.